Koeksistensi Hukum Adat Dan Hukum Negara Dalam Perlindungan Hutan Adat Di Desa Adat Tenganan Pegringsingan Karangasem Bali - Suwitra, Made (UI Scholars Hub, 2025)
Tenganan Pegringsingan Traditional Village is one of the Traditional Villages classified as Bali Mula/Bali Aga/Bali Tua Traditional Village in Karangasem Regency and the only traditional village that controls customary forests as village customs. Since 2019, with the issuance of the Decree of the Minister of Environment and Forestry of the Republic of Indonesia No. 1546/MENLHK-PSKL/PKTHA/KUM.1/2/2019, it has emphasized the recognition and respect for the right to manage and utilize customary forests, both as a production function and as a protection function. So the existence of Customary Villages as a legal entity in the management and utilization of village customary customs is still recognized and respected by the state according to its autonomous nature in the concept of coexistence. The profit-sharing model in the management of village customary land with cultivators is still traditionally carried out according to the results of the agreement by their ancestors since ancient times, so that in the concept of coexistence it is important to be made in writing in the development of state law to provide guarantees for certainty and protection in order to be able to provide benefits to prevent conflicts between the next generation of the two parties. Similarly, the construction of houses by cultivators in forest areas must be completed immediately within the village area